2022
DOI: 10.1021/acs.est.1c07996
|View full text |Cite
|
Sign up to set email alerts
|

Self-Defense Effects of Ti-Modified Attapulgite for Alkali-Resistant NOx Catalytic Reduction

Abstract: Nowadays, the serious deactivation of deNO x catalysts caused by alkali metal poisoning was still a huge bottleneck in the practical application of selective catalytic reduction of NO x with NH3. Herein, alkali-resistant NO x catalytic reduction over metal oxide catalysts using Ti-modified attapulgite (ATP) as supports has been originally demonstrated. The self-defense effects of Ti-modified ATP for alkali-resistant NO x catalytic reduction have been clarified. Ti-modified ATP with self-defense ability was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 53 publications
1
33
0
Order By: Relevance
“…Additionally, O 1s XPS spectra in Figure C were divided into two main feature peaks, namely chemisorbed oxygen (O α ) and lattice oxygen (O β ) . Since O α commonly migrated easily in the redox reaction and always considered as active oxygen species, ratios of O α /(O α + O β ) (F­(O α )) were also calculated based on the divided O 1s XPS spectra. The initial proportion of O α among CT was 20.36%, with it dropping significantly to 15.54% for Pb-CT, which resulted from the binding of Pb to CeO 2 that greatly reduced active oxygen species on the surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, O 1s XPS spectra in Figure C were divided into two main feature peaks, namely chemisorbed oxygen (O α ) and lattice oxygen (O β ) . Since O α commonly migrated easily in the redox reaction and always considered as active oxygen species, ratios of O α /(O α + O β ) (F­(O α )) were also calculated based on the divided O 1s XPS spectra. The initial proportion of O α among CT was 20.36%, with it dropping significantly to 15.54% for Pb-CT, which resulted from the binding of Pb to CeO 2 that greatly reduced active oxygen species on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, O 1s XPS spectra in Figure 2C were divided into two main feature peaks, namely chemisorbed oxygen (O α ) and lattice oxygen (O β ). 21 Since O α commonly migrated easily in the redox reaction and always considered as active oxygen species, 22…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…NH 3 temperature-programmed desorption mass spectra (NH 3 -TPD-MS) were used to study the surface acidity and quantify the acid amount of as-prepared catalysts, with the results demonstrated in Figure A. The MS signals for each catalyst were divided into four peaks, among which the desorption peaks below 200 °C represented weak acid sites, those at 200–400 °C represented medium-strong acid sites, and those above 400 °C represented strong acid sites. , It was observed that four NH 3 desorption peaks located at 177, 208, 260, and 350 °C emerged in the profile of CeO 2 /MMT-Ti. As for CeO 2 /TiO 2 , similar desorption peaks were also apparent at 180, 212, 267, and 350 °C.…”
Section: Resultsmentioning
confidence: 99%
“…The development of industry and transportation during past centuries increased significantly the emissions of nitric oxides (NO x ) to the atmosphere [1–3] . NO x causes several pollution issues like haze, ozone, acid rain, among others [4–7] . Nowadays, selective catalytic reduction (SCR) of NO x with ammonia is generally recognized as the most efficient technology for reducing the abatement of NO x [8–10] .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] NO x causes several pollution issues like haze, ozone, acid rain, among others. [4][5][6][7] Nowadays, selective catalytic reduction (SCR) of NO x with ammonia is generally recognized as the most efficient technology for reducing the abatement of NO x . [8][9][10] The commercial V 2 O 5 -WO 3 / TiO 2 catalysts have widespread application in coal-fired power plants because of the satisfactory SCR activity in temperature of 300-400 °C.…”
Section: Introductionmentioning
confidence: 99%